How Performance of Top Companies Are Related on IMD Digital Competitiveness Indicators? - Khazaei, Mehdi; Faghihi, Mahdi; Manesh, Vahid Sanaei (Issues in Social Science, 2024)
Given the role and importance of digital competitiveness indicators for businesses' performance and profitability, the question arises why international research in this field has been conducted infrequently. Therefore, the main purpose of the present study is to investigate the impact of digital competitiveness index on the financial performance of top companies in the world using performance theory and to evaluate the validity of IMD digital competitiveness index data. For this purpose, 175 top companies in the world from 2013 to 2018 that were profitable among the top 200 companies each year were selected as the statistical population. IMD digital Competitiveness reports and Fortune site were used to collect the data. Also the data analysis was done according to the panel data method using Stata15 software. The results show that in general, there is a positive relationship between IMD digital competitiveness index and financial performance of top companies in the world.